A novel evidence of Providencia alcalifaciens possessing the genotoxin colibactin - I. R. Matter; A. M. Alrawi; A. H. Al-Mola (Regulatory Mechanisms in Biosystems, 2025)
Cancer is one of the most threatening diseases to human health in the world. Consequently, this study was dedicated to shed light on an important part of this trend. Fifty five biopsies were collected from various sources, including stomach, colon, and rectal biopsies from the Gastrointestinal Endoscopy Department in Ibn Sina, Al-Jumhuri and Al-Bahth Hospitals, and surgical operations samples from patients with stomach and colon cancer from Al-Jumhuri Hospital and Al-Hayat Private Hospital in Mosul city ( Iraq ) . Among 61 bacterial isolates obtained in our study, they were all diagnosed as E. coli except one isolate diagnosed as Providencia alcalifecians as based on morphological examination and a Vitek II device. It was found that a high percentage of isolates carr ied the island genes ( clbA , clbB , clbN , and clbQ genes) for colibactin toxin (genotoxin) , which caus es host cell DNA damage and breaks, with 33 isolates possessing all the genes . P. alcalifaciens contained all genes studied depending on the PCR result. Our results show for the first time locally and globally the pre s en c e of genomic islands in P. alcalif a ciens responsible for the production of colibactin toxin . T he presence of these genes ha d not previously been diagnosed in such a potential pathogen.